2019
DOI: 10.1021/acssensors.9b01939
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Governed Debye Screening Length at the Solution-Solid Interface for Biosensing Applications

Abstract: Biosensors based on field-effect devices (bioFETs) offer numerous advantages over current technologies and therefore have attracted immense research over the decades. However, short Debye screening length in highly ionic physiological solutions remains the main obstacle for bioFET realization. This challenge becomes considerably more acute at the electrolyte−oxide interface of the sensing area due to high ion concentration induced by the charged amphoteric sites, which prohibits any attempt to employ the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…The application of negative V GR removes the surface excess cations and forms hole accumulation at the Si/SiO 2 interface to maintain charge neutrality across the EOI. In this way the ion concentration at the double layer is reduced and λ s is increased (for stronger electrolytes, see reference 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of negative V GR removes the surface excess cations and forms hole accumulation at the Si/SiO 2 interface to maintain charge neutrality across the EOI. In this way the ion concentration at the double layer is reduced and λ s is increased (for stronger electrolytes, see reference 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…A major recognized obstacle in the application of BioFETs is the screening length which is especially significant in highly-concentrated ionic solutions. 11–18 The screening length is identified with the Debye length ( λ D ) which at room temperature is represented as , where l B = 0.7 nm is the Bjerrum length, N Av is the Avogadro's number, z i and n B, i are the valence and solution concentration of ion type i , correspondingly, and the summation accounts for the various types of ions. 19 In a characteristic physiological solution, λ D = 1–2 nm which is significantly smaller than typical surface-bound antibody size (∼10 nm), for example, which seriously affects the possibility to sense target biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…This equation results in a value of 0.7 to 2.2 nm in a typical physiological sample, which is much smaller than the 5 to 10 nm length of an IgG antibody commonly used as a probe [39,40]. As a result, the charge of target molecules such as proteins or target DNAs is screened, making efficient sensing impossible [41]. This suggests that the size of the probe in BioFET can have a significant impact on sensitivity, so small probes like aptamers are often used recently rather than large probes, such as antibodies.…”
Section: Various Types Of Biofet Probes For Sensitivity and Adequate mentioning
confidence: 99%
“…Park et al [59] reported an interfacial charge regulation method by protein-blocking layers on ISFET for direct measurements in serum. Bhattacharyya et al [81] proposed a local electrostatic method to tune the Debye length, forcing the double layer ion concentration to match the bulk.…”
Section: Chemical Field Effect Transistor (Chemfet)-based Potential Smentioning
confidence: 99%